Recuperação de coagulante a partir da acidificação de resíduos gerados na Estação de Tratamento de Água do Rio Manso - Nelson Cunha Guimaraes (2005)
The majority of Water Treatment Plants (WTP) that operates in Brazil are conventional and produce residuals like settling tank sludge and filter wash-water. These residuals are generally discharged into a nearby natural water course without any kind of treatment. The investigationof alternatives to treat and dispose these residuals is a challenge due to the high costs involved in this process as well as the environmental impacts that come from improper practice. The coagulant recovery is an interesting alternative to treat residuals because 50 to 75% of sludges solids are iron and alum hydroxides that have elevated solubilities with acids. This work intends to study the feasibility of coagulant recovery process produced by acidification of Rio Manso WTP residuals, located near Belo Horizonte, MG. Laboratory solubility tests were done with residuals to recover alum and ferric chloride. The volume reduction of sludge was evaluated and jar tests with recovered coagulant were done.About 40% of sludge volume was reduced in alum and iron residuals. The recovered coagulants were similar to commercial coagulants to remove color and turbidity. The water treated with recovered aluminum sulfate didnt show increased metals concentration In Rio Manso taking pH, rotation, time of mixture and time of sedimentation estabilished todevelopment of this work as well as the afterward used of it in the recovered coagulant water treatment you get to conclusion that with alum recuperation its possible to reduce the costs with commercials coagulants up to 25%. The cost of ferric chlorine recovery are high anddidnt show economy.